Phenotypic and genetic diversity of Aeromonas Species isolated from fresh water lakes in Malaysia - Khor, W.C.; Puah, S.M.; Tan, J.A.M.A; Puthucheary, S.D.; Chua, K.H. (Public Library of Science, 2015)
Gram-negative bacilli of the genus Aeromonas are primarily inhabitants of the aquatic environment. Humans acquire this organism from a wide range of food and water sources as well as during aquatic recreational activities. In the present study, the diversity and distribution of Aeromonas species from freshwater lakes in Malaysia was investigated using glycerophospholipid-cholesterol acyltransferase (GCAT) and RNA polymerase sigma-factor (rpoD) genes for speciation. A total of 122 possible Aeromonas strains were isolated and confirmed to genus level using the API20E system. The clonality of the isolates was investigated using ERIC-PCR and 20 duplicate isolates were excluded from the study. The specific GCAT-PCR identified all isolates as belonging to the genus Aeromonas, in agreement with the biochemical identification. A phylogenetic tree was constructed using the rpoD gene sequence and all 102 isolates were identified as: A. veronii 43%, A. jandaei 37%, A. hydrophila 6%, A. caviae 4%, A. salmonicida 2%, A. media 2%, A. allosaccharophila 1%, A. dhakensis 1% and Aeromonas spp. 4%. Twelve virulence genes were present in the following proportions-exu 96%, ser 93%, aer 87%, fla 83%, enolase 70%, ela 62%, act 54%, aexT 33%, lip 16%, dam 16%, alt 8% and ast 4%, and at least 2 of these genes were present in all 102 strains. The ascV, aexU and hlyA genes were not detected among the isolates. A. hydrophila was the main species containing virulence genes alt and ast either present alone or in combination. It is possible that different mechanisms may be used by each genospecies to demonstrate virulence. In summary, with the use of GCAT and rpoD genes, unambiguous identification of Aeromonas species is possible and provides valuable data on the phylogenetic diversity of the organism.